Answer:
Therefore the particular solution of the given differential equation is
![Y(x)=(1)/(6) x^2 ln x](https://img.qammunity.org/2021/formulas/mathematics/college/46yvlg9lqcm85ucyd1c52pk61cjoshjhla.png)
Explanation:
The given ordinary differential equation is
![x^2y](https://img.qammunity.org/2021/formulas/mathematics/college/8rw9qun5m1t2wgidqn9jjwjfgrlgz66n22.png)
If y₁(x) =x² is a solution of ODE then it will be satisfy the ODE
y₁'(x)= 2x and y₁"(x)=2
Putting the value of y₁'(x) and y₁"(x) in x²y"-3xy'+4y=0 we get
x².2-3x.2x+4x²= 2x²-6x²+4x²=0
Therefore y₁(x) is a solution of the given differential equation.
Again,
y₂(x) =(x²ln x ) is a solution of ODE then it will be satisfy the ODE.
![y'_2=2x ln x+ x^2*(1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/college/3fkti2k8phe18g6zw22yll4n6mtz34jyfs.png)
![= 2x ln x+x](https://img.qammunity.org/2021/formulas/mathematics/college/d26ofxd4f18krz79zd7m2slvpi5r9fe3uj.png)
= 3+2 ln x
Putting the value of y₂'(x) and y₂"(x) in x²y"-3xy'+4y=0 we get
=0
Therefore y₂(x) is a solution of the given differential equation.
The wronskian of y₁(x) and y₂(x) is
![W(y_1,y_2)(x)=\left|\begin{array}{cc}y_1&y_2\\y'_1&y'_2\end{array}\right|](https://img.qammunity.org/2021/formulas/mathematics/college/ecbvlad328w1dlagwjqk0bl7xksctrvj8h.png)
![=\left|\begin{array}{cc}x^2&x^2 ln x\\2x&2x ln x+x\end{array}\right|](https://img.qammunity.org/2021/formulas/mathematics/college/10n5425kh21p7z43rjcfrz0nskf6hqubxd.png)
=x²(2x ln x+x)-x²ln x(2x)
=2x³ ln x +x³ - 2x³ln x
=x³≠0
Here
![g(x)=(y_2(x))/(y_2(x)) = ln x](https://img.qammunity.org/2021/formulas/mathematics/college/o7eihvbhwwv5a8ph4elknr9vx1373t4w70.png)
The particular solution is
![Y(x)=- y_1(x)\int(y_2(x).g(x))/(W(y_1,y_2)(x))dx + y_2(x)\int(y_1(x).g(x))/(W(y_1,y_2)(x))dx](https://img.qammunity.org/2021/formulas/mathematics/college/b7i0uqtiy7t1nazwlquqdjtdfzbk7g4h0f.png)
![=-x^2\int ((lnx)^2)/(x) dx+x^2 ln x\int (ln x)/(x) dx](https://img.qammunity.org/2021/formulas/mathematics/college/x3m3svrbznatlybxqao0gs6llm84c4y8ow.png)
Let ln x =u
![\Rightarrow (1)/(x) dx=du](https://img.qammunity.org/2021/formulas/mathematics/college/v9op7s605kaeya9x6xv7xlo7f1m77m7zo5.png)
![=-x^2 (u^3)/(3) +x^2 ln x (u^2)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/ij5wloicwbyga5e5ejkrqzrf65kj02qni4.png)
![=-(x^2(lnx)^3)/(3) +(x^2(lnx)^3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/v5jjtqpme8wp0aba6cd4dvfcnwlag2u4mk.png)
![=(1)/(6)x^2 (ln x)^3](https://img.qammunity.org/2021/formulas/mathematics/college/lgtzvb1k02akzld8rjx6g2f7m02rio3bu0.png)
Therefore the particular solution of the given differential equation is
![Y(x)=(1)/(6) x^2 ln x](https://img.qammunity.org/2021/formulas/mathematics/college/46yvlg9lqcm85ucyd1c52pk61cjoshjhla.png)